Lab measures of other-regarding preferences can predict some related on-the-job behavior: Evidence from a large scale field experiment - Stephen V. Burks; Daniele Nosenzo; Jon Anderson; Matthew Bombyk; Derek Ganzhorn; Lorenz Götte; Aldo Rustichini (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2015)
There is by now ample evidence from laboratory experiments that individuals exhibit "prosocial" or "other-regarding" preferences. However, a key question is whether the importance of other-regarding preferences documented in the laboratory can be readily generalized to draw conclusions about the importance of such preferences outside the laboratory, where markedly different conditions often apply (for instance, differences in stakes; differences in the level of anonymity and scrutiny; etc). In this paper we address this question by using a measure of costly cooperation elicited in a laboratory experiment to predict the cooperative behaviours that the same individuals exhibit in comparable, naturally-occurring, social situations outside the laboratory. In this Nottingham School of Economics working paper, Daniele Nosenzo and co-authors conducted laboratory experiments with 645 subjects at a trucker training program in the Midwestern US. The experiment use a version of the prisoner's dilemma game to measure subjects' preferences for cooperation. The authors observe the same subjects on the job for up to two years afterwards in two naturally-occurring choices - whether to send two types of satellite uplink messages from their trucks. The first identifies trailers requiring repair, which benefits fellow drivers, while the second benefits the experimenters by giving them some follow-up data. The authors find that individual differences in costly cooperation observed in the lab do predict individual differences in the field in the first choice but not the second. Daniele Nosenzo and co-authors suggest that this difference is linked to the difference in the social identities of the beneficiaries (fellow drivers versus experimenters), and conjecture that whether or not individual variations in pro-sociality generalize across settings may depend in part on this specific contextual factor: whether the social identities, and the relevant prescriptions (or norms) linked to them that are salient for subjects are appropriately parallel.
Keywords: B4; C9; D03; 330; experiments; generalizability; external validity; parallelism; social identity; other-regarding behavior; costly cooperation; social preferences; prisoners' dilemma; trucker; truckload